A novel LMNA nonsense mutation causes two distinct phenotypes of cardiomyopathy with high risk of sudden cardiac death in a large five-generation family. Issue 12 (26th June 2018) - Glöcklhofer, Christina R; Steinfurt, Johannes; Franke, Gerlind; Hoppmann, Anselm; Glantschnig, Theresa; Perez-Feliz, Stefanie; Alter, Svenja; Fischer, Judith; Brunner, Michael; Rainer, Peter P; Köttgen, Anna; Bode, Christoph; et al.
Abstract: Aims: Characterization of the cardiac phenotype associated with the novel LMNA nonsense mutation c.544C>T, p.Q182*, which we have identified in a large five-generation family. Methods and results: A family tree was constructed. Clinical data [arrhythmia, syncope, sudden cardiac death (SCD), New York Heart Association (NYHA) class] were collected from living and deceased family members. DNA of 23 living family members was analysed for mutations in LMNA . Additionally, dilated cardiomyopathy multi-gene-panel testing and whole exome sequencing were performed in some family members to identify potential phenotype-modifiers. In this five-generation family ( n  = 65), 17 SCDs occurred at 49.3 ± 10.0 years. Furthermore, we identified eight additional mutation-carriers, seven symptomatic (44 ± 13 years), and one asymptomatic (44 years). First signs of disease [sinus bradycardia with atrioventricular (AV)-block I°] occurred at 36.5 ± 8.1 years. Paroxysmal atrial fibrillation (AF) (onset at 41.8 ± 5.7 years) rapidly progressed to permanent AF (46.2 ± 9.8 years). Subsequently, AV-conduction worsened, syncope, pacemaker-dependence, and non-sustained ventricular tachycardia (43.3 ± 8.2 years) followed. Ventricular arrhythmia caused SCD in patients without implantable cardioverter-defibrillator (ICD). Patients protected by ICD developed rapidly progressive heart failure (45.2 ± 10.6 years). A different phenotype was seen in a sub-family in three patients with early onset of rapidly decompensating heart failure and only minor prior arrhythmia-related symptoms. One patient received high-urgency heart transplantation (HTX) at 32 years, while two died prior to HTX. One of them developed lethal peripartum-associated heart failure. Possible disease-modifiers were identified in this 'heart failure sub-family'. Conclusion: The novel LMNA nonsense mutation c.544C>T causes a severe arrhythmogenic phenotype manifesting with high incidence of SCD in most patients; and in one sub-family, a distinct phenotype with fast progressing heart failure, indicating the need for early consideration of ICD-implantation and listing for heart-transplantation.